Measurement of the coherence length of sputtered Nb0.62Ti0.38N thin films. - Lei Yu (IEEE Transactions on applied superconductivity)
Superconducting and normal state properties of the useful film material NbxTi1-xN have been characterized. In particular, the coherence length of reactively sputtered Nb0.62Ti0.38N thin films is determined to be 2.4±0.3 nm. The results are inferred from fitting the de Gennes-Werthamer theory to experimental measurements of the proximity-induced depression of the transition temperature in Nb-Nb0.62Ti0.38N-Nb structures. The coherence length, as defined by this theory, can be used to infer the zero-temperature Ginzburg-Landau coherence length, ξGL (0), of 3.8 nm for the Nb0.62Ti0.38N synthesized in this study. The shorter coherence length and lower resistivity of these films, when compared to NbN, indicates that they are an appealing choice for electrodes in rapid single flux quantum circuits.